Digital Transformation and Human Resource Development Strategies to Enhance the Global Competitiveness of the Halal Industry - Putra, Trisno Wardy; Siradjuddin, Siradjuddin; Lutfi, Mukhtar (Journal of Management and Business Innovations, 2024)
This study examines digital transformation and human resource (HR) development in the halal industry through a systematic approach. The main objective of this study is to understand how digital technology and HR development are implemented in the halal industry sector, as well as the challenges and opportunities that arise in the process. The research method uses qualitative with a literature study approach, including searching for relevant literature in various academic databases, critical analysis of the collected literature, and synthesizing the resulting findings. This study found that although digital transformation provides many opportunities, the success of its implementation is highly dependent on the development of employee digital skills and changes in organizational culture that support innovation. Thus, the results of this study are expected to provide new insights for the development of effective digital transformation strategies in increasing the competitiveness of the halal industry at the global level. Keywords: Digital transformation, Halal industry, Human Resources.